(untitled) (UNED Research Journal, 2017)
Parks and other green spaces improve the physical and mental health of the city dwellers, but in Costa Rica little is known about how those spaces are perceived by their users. Here we analyze the influence of sex on use and perception of safety and maintenance in a large and representative sample of Costa Rican parks (27 municipal parks randomly chosen). We interviewed 30 visitors per park with a validated survey. We found that, regardless of lighting level and degree of vegetation cover, women feel unsafe at all times in the parks. They believe that crimes are common –even though very few have actually been victims– and they are less satisfied than men with park maintenance and safety. Our results are similar to those obtained in Latin America and other regions.